Feasibility and mechanism analysis of Reduning in the prevention of sepsis-induced pulmonary fibrosis - Wang, Ziyi; Liu, Yuxin; Chen, Feng; Liao, Haiyan; Wang, Xuesong; Guo, Zhe; Wang, Zhong (Frontiers in Pharmacology, 2022)
Abstract: Object: To explore the possibility and possible targets of Reduning in the prevention of sepsis-related pulmonary fibrosis. Methods：The active components and targets of Reduning were searched and screened from the database and analysis platform of traditional Chinese medicine (TCM) system pharmacology. GeneCards human genome database, DisGenet database, and OMIM database were applied to determine the targets associated with sepsis-induced pulmonary fibrosis. DAVID Bioinformatics Resources 6.8 was used for GO and KEGG enrichment analysis to predict its possible signaling pathways and explore its molecular mechanism. The protein-protein interaction (PPI) network was employed to identify key active components and core targets. Molecular docking technology was applied to screen the complexes with stable binding of key active components and core targets. Molecular dynamics simulations were used to verify the binding stability and molecular dynamics characteristics of the complexes. The protective effect of RDN on sepsis-induced pulmonary fibrosis were verified by in vitro and in vivo experiments. Results: There were 319 shared targets between sepsis-induced pulmonary fibrosis and RDN. GO enrichment analysis showed that they mainly regulated and participated in the positive regulation of kinase activity, mitogen-activated protein kinase (MAPK) cascade and protein phosphorylation. KEGG enrichment analysis showed that they were mainly enriched in MAPK cascade signaling pathway, calcium signaling pathway, apoptosis pathway and other signaling pathways. The results of molecular docking and molecular dynamics simulations showed that the active components stigmasterol, beta-sitosterol, and quercetin had good binding activities with ERBB2 and exhibited good stability. Molecular validation experiments confirmed RDN could alleviated lung fibrosis induced by cecum ligation and puncture (CLP), parallel with the inhibition of ERBB2-p38 MAPK pathway in mouse alveolar macrophages (AMs). Conclusion: Reduning may prevent sepsis-induced pulmonary fibrosis by regulating ERBB2-p38 MAPK signaling pathway, which provides a possibility for the prevention of sepsis-induced pulmonary fibrosis with TCM.